Loanwords in Hovhannes Tlkurantsi’s Poems - Grigoryan, Susanna (Bulletin of Yerevan University B: Philology, 2022)
The study of the literary monuments of Medieval Armenia provides important material for the history of the Armenian language. The lexical stock of the Middle Armenian language was constantly replenished and enriched in the course of development, reflecting the changes taking place in the life of the people. This period is quite rich in borrowings that survived and have been enrooted in the language due to the cultural, political and commercial ties of the Armenian people with other peoples. What has been said, can be unconditionally attributed Hovhannes Tlkurantsi’s poems; he developed a wide literary activity. The lexicon of H. Tlkurantsi’s poems is rich and varied. He is one of the first published authors of medieval poetry. Tlkurantsi composed more than forty poems, which are distinguished by their artistic merit. His poems are abundant in Arabic, Persian, Turkish, Greek borrowings. They remained in the vocabulary of the Armenian dialects or eventually merged with the literary language and became a living element of its vocabulary with some phonetic or semantic differences. The purpose of this article is to study the borrowings used by him, to clarify the scope of their usage, as well as to identify their semantic features.